Profile of intestinal fungal microbiota in acute pancreatitis patients and healthy individuals - Meng-Qi Zhao; Miao-Yan Fan; Meng-Yan Cui; Su-Min Chen; Jing-Jing Wang; Ying-Ying Lu; Qiao-Li Jiang (Gut Pathogens)
Abstract Objective The gut is involved in the development of acute pancreatitis (AP). Increased focus is being given to the role of gut microbiota in the pathogenesis of AP. Nevertheless, there is currently no available evidence regarding the composition of fungal microorganisms in the intestines of patients with AP. Methods In this study, we sequenced ITS rRNA gene amplicons and examined the intestinal fungal microbiota in feces from 11 AP patients (the test group) and 15 healthy people (the control group). Additionally, we examined the relationship between fungus and clinical and biochemical markers. Results Results showed a decline in alpha diversity in AP patients. The overall fungal microbiota in the test group was significantly different from that of the control group (P < 0.05). In both groups, the fecal fungal microbiota was dominated by Ascomycota and Basidiomycota phyla. At the genus level, the abundance of Candida was significantly higher in the test group and the abundances of Penicillium, Auricularia, unclassified Eurotiomycetes, Epicoccum and Vishniacozyma were significantly lower. Furthermore, AP patients had a significant decrease in the GMHI score and a significant increase in the MDI index. The co-abundance networks of gut fungus in AP patients showed more interactions and mostly positive correlations than in the control group. There was a strong positive link between Aspergillus and WBC counts, while There was a strong link between unclassified Rozellomycota and IL-6. Conclusion Our study provides the first empirical evidence that AP patients have different fecal fungal microbiota, which raises the possibility that mycobiota contribute to the etiology and progression of AP.